Grain-tilled change of fruit short rotation of crops Western Steppe of Ukraine marked negative balance of sulfur. Organo-mineral system of fertilizer with the introduction of 40 t/ha manure + 15 t/ha of green manure + 5 t/ha of straw + N50P85K113 and sat - Лопушняк, В. І. (Scientific Progress & Innovations, 2014)
Grain-tilled change of fruit short rotation of crops Western Steppe of Ukraine marked negative balance of sulfur. Organo-mineral system of fertilizer with the introduction of 40 t/ha manure + 15 t/ha of green manure + 5 t/ha of straw + N50P85K113 and saturation of crop rotation by organic fertilizers (15,0 t/ha) provides a positive balance of sulfur – up to 10 kg/ha of area of crop rotation. By the most bearing-out of sulfur in grain-tilled change of fruit of crop rotation marked sugar beet and red clover, with which the main and side products makes up 80 % of total removal of this element by all cultures.